The Role of Student Counseling in Developing Role Model Perception for Female Students in Jeddah Province Education Schools in the Kingdom of Saudi Arabia - Al- Turkistani, Sara Abdullah; Akram, Hadeel Abdulah (Journal of Educational and Psychological Sciences, 2020)
This study aimed to identify the role of student counseling in developing role model perception for female students in Jeddah Province education schools in the Kingdom of Saudi Arabia, and their concept of role model, and whether there were statistically significant differences about the role of student counseling in the development role model concept among students according to variables as education grade, education type and specialization. The number of participants in the study was (202) girl’s students in both secondary and high school in Jeddah. The researcher prepared measures of role model according to the ideal role model that was prepared by Ghanim (2001), and the measure of the role of student counseling in the development of perception of role model. The results of the present study showed a positive relationship between the role of student counseling and the development of the concept of role model among the students. There were also statistically significant differences in the role of student counseling in development of perception about the role model among general education students according to grade of education (third preparatory versus third secondary grade), Meanwhile, there were insignificance difference according to type of education (governmental- civil) and variable specialization (scientific- literary).